Evolution of Research Ethics in a Low Resource Setting: a case of Uganda - Ochieng, Joseph; Kwagala, Betty; Sewankambo, Nelson; Mwaka, Erisa (Developing world bioethics, 2020)
The globalization of clinical research in the last two decades has led to a significant increase in the volume of clinical research in developing countries. As of 2016, Uganda was the third largest destination for clinical trials in Africa. This requires adequate capacity and systems to facilitate ethical practice. Methods: This was a retrospective study involving review of laws, guidelines, policies and records from 1896 to date. Results: Modern medicine evolved from 1896 and by the time of Uganda’s independence in 1962, a 1500 bed national referral hospital was in place and a fully-fledged medical school was established at the Makerere University. As the practice of medicine evolved in the country, so did medical research that addressed priority health issues. The growth in modern medicine was not matched with development of research infrastructure and regulatory systems. The first documented regulation of research activities was in 1970 while the first research ethics committee established in 1986 was to facilitate review of research related to the HIV/AIDs pandemic. In 1990 an Act of Parliament was passed to facilitate development and implementation of policies, hence the development of the national guidelines in 1997, training, establishment and accreditation of research ethics committees, conferences and research site monitoring.
Keywords: evolution; research ethics; Uganda